TINJAUAN YURIDIS TERHADAP KEWAJIBAN PENYIDIK DALAM MENGIRIMKAN SURAT PEMBERITAHUAN DIMULAINYA PENYIDIKAN KE KEJAKSAAN NEGERI PEKANBARU - Hanif, Dean Prakasa; Deliana, Evi; R, Mukhlis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2019)
The National Police occupies a position as law enforcer in accordance with the principles offunctional differentiation outlined in the Criminal Procedure Code. Polri as a general criminal investigatorthat has a connection with the criminal justice system, namely in the case of a Notice of Commencement ofInvestigation, hereinafter abbreviated as SPDP. The reality that often occurs in the investigation of criminaloffenses is the delay in sending SPDP to the public prosecutor. Through the ruling of the ConstitutionalCourt Number 130 / PUU-XIII / 2015 there is an obligation for investigators to submit SPDP not only to thepublic prosecutor but also to the reported party and the victim a maximum of 7 (seven) days after theissuance of the investigation warrant. The problem in this study is how the mechanism and implementationof the obligation of investigators to submit a notification letter on the commencement of investigation intothe public prosecutor and what are the legal consequences and efforts made by the Pekanbaru stateprosecutor on the violation of sending notification letters to the start of the investigationThis study uses a normative juridical approach and empirical jurisdiction. Data is obtainedthrough library studies and through interviews using written guidelines for specified sources. This researchwas conducted at the Pekanbaru state prosecutor's office and the pekanbaru police station in 2018-1019,with resource persons consisting of investigators at the Pekanbaru police station and prosecutors at thePekanbaru state prosecutor's office.The results of the research and discussion can be concluded that the mechanism and obligation ofinvestigators in sending SPDP are contained in Article 109 paragraph (1) of the Criminal Procedure Codeand the Constitutional Court decision No. 130 / PUU-XIII / 2015 and the legal consequences and efforts ofthe Pekanbaru state prosecutor on violations of SPDP deliveries where the public prosecutor can reject theSPDP whose notification has passed the 7 (seven) day deadline since the investigation began. Further legalconsequences of law enforcement cannot be realized, because the public prosecutor has not yet known thatthe investigator has begun investigating a case so that the party who feels disadvantaged can submit a pretrialas a further legal remedy.Keywords: Obligations of Investigators to Send SPDP-Prosecutors-Legal Effects.